EnMS and EMIS: What's the Difference?. Issue 6 (1st September 2016) - Brogan, Mike; Monaghan, Paul F.
ABSTRACT: This article focuses on clearly identifying the two different ways that the expression "energy management system" is commonly used today. The conclusion is that future confusion may be eliminated by use of the terms: energy management system (EnMS); and energy management information system (EMIS).